2013
DOI: 10.1097/jto.0b013e318287c943
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Treatment Outcomes of Intraventricular Chemotherapy in 105 Patients for Leptomeningeal Carcinomatosis from Non–Small-Cell Lung Cancer

Abstract: Intraventricular chemotherapy for patients with LMC from non-small-cell lung cancer could palliate associated symptoms and prolong patients' survival. Careful selection of patients for intraventricular chemotherapy is recommended with aggressive ICP control and concurrent systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 30 publications
7
70
3
1
Order By: Relevance
“…I n the LMC literature, generally most patients were reported to survive only 3-4 months after the diagnosis with exceptional longer survival reports of up to 2 years [6,[16][17][18]. For instance, although the authors reported excellent 18 and 14 month median OS in two small subgroups receiving I TT or TKI , the median OS was only 3 months in the whole study cohort of Morris et al [6], which was comparable to our finding of 3.9 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…I n the LMC literature, generally most patients were reported to survive only 3-4 months after the diagnosis with exceptional longer survival reports of up to 2 years [6,[16][17][18]. For instance, although the authors reported excellent 18 and 14 month median OS in two small subgroups receiving I TT or TKI , the median OS was only 3 months in the whole study cohort of Morris et al [6], which was comparable to our finding of 3.9 months.…”
Section: Discussionsupporting
confidence: 91%
“…The prognostic impact of parenchymal BM in LMC patients is an area of active research [16,25,26]. Particular to LMC of NSCLC, parenchymal BM is present in more than 50 % of cases.…”
Section: Fig 2 Overall Survival In 51 Patientsmentioning
confidence: 99%
“…In order to palliate LMrelated neurological symptoms, WBRT is occasionally effective, but does not appear to provide a relevant survival benefit [6]. A few retrospective studies suggested effectiveness of intrathecal chemotherapies, but no clear evidence has been confirmed by prospective trials [7,8]. Unfortunately, few established therapeutic options are administered for NSCLC complicated with LM without driver oncogene…”
Section: Introductionmentioning
confidence: 98%
“…In the treatment of LC, surgery and radiotherapy have only a limited role and they are mainly deserved for palliation of hydrocephalus or symptoms resulting from focal lesions, whereas intrathecal or systemic chemotherapy are more widely used (77). Although some retrospective studies suggested an improvement in symptomatic palliation and a survival benefit with intrathecal chemotherapy for LC (76,78), the optimal dose and schedule as well as the real efficacy of intrathecal chemotherapy remain elusive, due to the lack of large randomized clinical trials (74).…”
Section: Chemotherapy As Salvage Treatment For Progressive Bmsmentioning
confidence: 99%